The sociological approach to Islamic da'wa - Farooqui, Jamil (International Islamic University Malaysia, 2014)
Da'wah has been studied from different angles and from different points of view. The present paper deals with the sociological approach to Da'wah. It focuses on three aspects of Da'wah which has wide repercussions and a determinant impact on social relations and life of individuals. First, the significance of Da'wah from the sociological perspectives is the nature of intellectual interaction where there is an exchange of ideas and ideals affecting the mind-set of individuals. Second, it is the vital form of social transformation which takes place at the intellectual level and proceeds to the physical level. Third, it has a distinct mehtod based on the communicator, content, recepient and the style of communication.